The MX-Helix of Muscle nAChR Subunits Regulates Receptor Assembly and Surface Trafficking - Rudell, Jolene Chang; Borges, Lucia Soares; Yarov-Yarovoy, Vladimir; Ferns, Michael (Frontiers in Molecular Neuroscience, 2020)
Nicotinic acetylcholine receptors (AChRs) are pentameric channels that mediate fast transmission at the neuromuscular junction (NMJ) and defects in receptor expression underlie neuromuscular disorders such as myasthenia gravis and congenital myasthenic syndrome (CMS). Nicotinic receptor expression at the NMJ is tightly regulated and we previously identified novel Golgi-retention signals in the beta and delta subunit cytoplasmic loops that regulate trafficking of the receptor to the cell surface. Here, we show that the Golgi retention motifs are localized in the MX-helix, a juxta-membrane alpha-helix present in the proximal cytoplasmic loop of receptor subunits, which was defined in recent crystal structures of cys-loop receptor family members. First, mutational analysis of CD4-MX-helix chimeric proteins showed that the Golgi retention signal was dependent on both the amphipathic nature of the MX-helix and on specific lysine residues (betaK353 and deltaK351). Moreover, retention was associated with ubiquitination of the lysines, and betaK353R and deltaK351R mutations reduced ubiquitination and increased surface expression of CD4-beta and delta MX-helix chimeric proteins. Second, mutation of these lysines in intact beta and delta subunits perturbed Golgi-based glycosylation and surface trafficking of the AChR. Notably, combined betaK353R and deltaK351R mutations increased the amount of surface AChR with immature forms of glycosylation, consistent with decreased Golgi retention and processing. Third, we found that previously identified CMS mutations in the epsilon subunit MX-helix decreased receptor assembly and surface levels, as did an analogous mutation introduced into the beta subunit MX-helix. Together, these findings indicate that the subunit MX-helix contributes to receptor assembly and is required for normal expression of the AChR and function of the NMJ. In addition, specific determinants in the beta and delta subunit MX-helix contribute to quality control of AChR expression by intracellular retention and ubiquitination of unassembled subunits, and by facilitating the appropriate glycosylation of assembled surface AChR.